AL-GHAZALI DAN PEMIKIRANNYA TENTANG PENDIDIKAN TASAWUF - Saputra, Tomi; Wahid, Annisa (ILJ: Islamic Learning Journal, 2023)
This research aims to uncover Al-Ghazali's thoughts on Sufism and unveil and to highlight Al-Ghazali's role in the development of Sufism as an academic discipline and spiritual movement within the Islamic world. The methodology employed in this study involves literature review and analysis of Al-Ghazali's works, particularly his seminal work "Ihya Ulum al-Din" (Revival of the Religious Sciences). The results of this study indicate that Al-Ghazali regarded Sufism as a means to achieve self-realization and the highest spiritual goals through the integration of knowledge and mystical experiences. Al-Ghazali's understanding of the relationship between human will and the divine will, as well as the significance of overcoming desires and ego in attaining spiritual perfection, is also illuminated. His significant contributions in developing Sufism as an academic discipline and spiritual movement are evident through his influential writings.